Peran Penggunaan Mobile Banking dalam Memediasi Financial Behaviour terhadap Financial Well-Being - Nabila Ayu Wijayanti; Liana Mangifera (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Current developments influence technological developments, especially in the financial sector. Technological developments also have an impact on the Indonesian banking sector, as evidenced by the existence of Mobile Banking technology which is currently being developed in society. Mobile Banking also provides many services such as checking account balances, transfers, electricity bill payments, top up credit, top up e-wallet, etc. The purpose of this research is all types of mobile banking in Indonesia, such as Bank BRI with BRIMO Mobile Banking, BCA with BCA mobile or MyBCA, BNI with BNI Mobile Banking, Bank Jateng with BIMA, and so on. This research will discuss the influence of using mobile banking as a mediation to link the impact of financial behavior (financial efficacy, financial attitudes, and financial knowledge) on financial well-being.